The information field management during the period of interstate confrontation - A. V. Aristov (Современная наука и инновации)
The article analyzes topical issues of practical activity in the field of information support for the activities of government agencies, public and business organizations in the context of their participation in solving large-scale tasks of interstate confrontation.The management of the information field is considered in the article as one of the most important areas of activity and can be implemented either on the territory of warring/adjacent states, on the territory of countries that are used as an arena for struggle, or in "extraterritorial" spaces, one of which is the information space. Within the framework of the current socio-political discussion in Russia, various experts often voice the opinion that Russia has never been distinguished by "high" competencies in conducting information warfare. The author of the article, using the example of specific historical "paradoxes", refutes this myth and comes to the conclusion that in the history of our country there are many examples of successful information campaigns that have positively affected the course of a particular military-political confrontation. Moreover, an analysis of the experience of Russia's "informational" participation in conflicts of different eras allows us to conclude that the country has both positive and negative experience in implementing such projects. According to the author of the article, at the current moment, one of the most promising forms of political participation in the process of information warfare is the management of the information field. Primarily due to the use of its resonant potential, the effect of novelty in the information used and/or a variety of triggers. Such political participation ultimately leads to the emergence of numerous information flows and can be determined by one or another chosen scenario. There are three main types of scenarios (essay scenario, analytical scenario, graphic scenario), which differ from each other both in the set of properties of the text itself and in what technological means can be used in the preparation of scenarios. At the same time, any scenario is built in the logic of one of two alternatives: "from the object" or "from the process". An attempt to build a scenario from a "process" within the framework of an information confrontation essentially means an attempt to exert targeted influence on the initiator of even a separate local information flow in order to stop a specific problem. As for the construction of the "from the object" scenario, this approach, for example, may involve the perception of the opposing elite as a whole and setting the task of causing damage to it, for example, in the electoral field. The logic of building a scenario contains 3 stages: the creation of a theoretical model, the design of a practical model, and the definition of alternatives for the development of the scenario.